104k views
3 votes
Solve 5h + 2(11 - h) = -5 (Find h. Explain each step please.)

2 Answers

6 votes

Answer:

h = -4.5

Explanation:

5h + 2(11-h) = -5

5h + 2(11-h)

+h +h

6h + 2 x 11 = -5

6h + 22 = -5

- 22 -22

6h = -27

/6 /6

h = -4.5

I hope this helps, I know the explanation is kinda confusing but I tried my best to explain :))

User Lucasasecas
by
6.0k points
2 votes

Answer:

h = -9

Explanation:

Distribute the 2 to the parentheses:

5h + 2(11 - h) = -5

5h + 22 - 2h = -5

Add like terms:

3h + 22 = -5

3h = -27

h = -9

User Arok
by
6.1k points